Effectiveness Of Gboard Application on Motivation to Learn Indonesian Language Through Direct Learning - Mariono, Andi; Kristanto, Andi; Vatosoa Idaly, Randrianatolotriniavonirina Mendrika (Belantika Pendidikan, 2023)
This study investigates the influence of the Gboard application, a virtual keyboard that provides immediate translation of voice or text on motivation for language learning. This study centers on the acquisition of the Indonesian language through the usage of English. This research aims to determine how the use of the Gboard application effects motivation to learn Indonesian. The research was carried out among students from different countries learning Bahasa Indonesia in 2023. This quantitative research employs an online survey utilizing Likert scales. The results suggest that the majority of students who utilize Gboard for social media conversations with Indonesians people perceive it as beneficial for enhancing their proficiency in the Indonesian language. Consequently, Gboard has been regarded as a highly efficient educational system. A significant number of participants have reported an impressive increase in their motivation to learn Indonesian, attributing it to the utilization of Gboard. The study concludes that Gboard, when combined with the direct learning model, greatly enhances language learning motivation among foreign students. The result emphasizes the crucial role of technology, specifically Gboard, in augmenting motivation. These insights are advantageous for educators and academics seeking to use technology into learning a new language.